Pengaruh Instrumen Moneter Syariah dan Ekspor Terhadap Pertumbuhan Ekonomi di Indonesia - Asnuri, Wulan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
The aim from this research is to analyze the effect of total financing in Islamic banking (PEM), Sharia Certificate of BankIndonesia (SBIS) and export contribution to economic growth in Indonesia. The method that used in this study is error correction model (ECM). The result showed that in short-run SBIS gave a negative impact to economic growth, otherwise the total financing and export contribution didn’t have an impact to economic growth. In the long-run, total financing, SBIS, and export contribution have a negative impact to Indonesian economic growthDOI: 10.15408/aiq.v5i2.2569